Leaf cytokinin accumulation promotes potato growth in mixed nitrogen supply by coordination of nitrogen and carbon metabolism. (November 2022) - Zhang, Wei; Wu, Xu; Wang, Daojian; Wu, Daxia; Fu, Yihan; Bian, Chunsong; Jin, Liping; Zhang, Yali
Abstract: The source and sink balance determines crop growth, which is largely modulated by nitrogen (N) supplies. The use of mixed ammonium and nitrate as N supply can improve plant growth, however mechanisms involving the coordination of carbon and N metabolism are not well understood. Here, we investigated potato plants responding to N forms and confirmed that, compared with sole nitrate supply, mixed N (75 %/25 % nitrate/ammonium) enhanced leaf area, photosynthetic activity and N metabolism and accordingly resulted in outgrowth of stolons and shoot axillary buds. Cytokinin transportation in xylem sap and local cytokinin synthesis in leaves were up-regulated in mixed-N-treated potato plants relative to sole nitrate provision; and exogenous application of 6-benzylaminopurine in addition to sole nitrate restored leaf area, photosynthetic capacity and N content in leaves to the similar as those under mixed-N treatment. Partial defoliation, an effective method to enhance the sink strength, induced more cytokinin content in leaflets under two treatments relative to their respective controls and ultimately resulted in larger photosynthesis capacity and leaf area. These results suggest that mixed-N-enhanced plant growth through the coordination of carbon and N metabolism largely depends on the signal molecule cytokinin modulated by N supplies. Highlights: Mixed N forms enhanced leaf growth, photosynthetic activity and N metabolism relative to sole N forms and accordingly resulted in outgrowth of stolons and shoot axillary buds. Improvement of cytokinin transportation in xylem sap and local cytokinin synthesis in leaves has been suggested to participate in mixed-N-regulated coordination of C assimilation and utilization.